Marketing lessons from the Grateful Dead what every business can learn from the most iconic band in history - Scott, David Meerman (Wiley, 2010)
"The Grateful Dead broke almost every rule in the music industry book ... By cultivating a dedicated, active community, collaboration with their audience to co-create the Deadhead lifestyle, and giving away 'freemium' content, the Dead pioneered many social media and inbound marketing concepts successfully used by businesses across all industries today. Written by marketing gurus and lifelong Deadheads David Meerman Scott and Brian Halligan, 'Marketing Lessons from the Grateful Dead' gives you key innovations ... you can apply to your business ..."--Page 4 of cover
Includes bibliographical references (page 159). - Print version record
Keywords: Grateful Dead (Musical group); Marketing; Social media -- Economic aspects; Success in business; Médias sociaux; Aspect économique; Succès dans les affaires; marketing; BUSINESS & ECONOMICS; Green Business; Social media; Economic aspects